ANALYZING SOCIO-ECONOMIC RECOVERY ON SUMATRA ISLAND POST-COVID-19: A SPATIAL DURBIN MODEL APPROACH - Lubis, Ibrah Hasanah; Mahdi, Saiful; Munawar, Munawar (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2024)
The COVID-19 outbreak was designated as a public health emergency that disturbed the world from January 2020 to May 2023 by the World Health Organization. This outbreak has drastically changed the order of socio-economic life. According to data Gross Domestic Product, it was recorded to grow by 5.03% in 2023 according to data from the Central Statistics Agency, which is still slightly below the pre-pandemic level of 5.17% in 2018. At the regional level, only 6 provinces experienced a higher Gross Regional Domestic Product growth rate in 2023 compared to 2018. These figures highlight the need for recovery efforts to be made to restore the condition of the community and the environment so that the socio-economic activities of the community can run well again. This study uses Google mobility report data and panel data spatial regression analysis to determine the factors that influence socio-economic recovery on the island of Sumatra and how the influence between regions in the recovery effort. The data used is panel data for 273 observation days in eight provinces. By integrating spatial panel data methods with mobility-based proxies, this approach offers a new framework that is rarely applied in studies of post-COVID-19 socio-economic recovery in Sumatra.